Legal Policy Model for Prevention Children Marriage at West Nusa Tenggara Province - Sri Karyati; B. Farhana K.Lestari (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
Until now the issue of child marriage in NTB has not yet been resolved. The issue of child marriage in NTB has not been completed because the roots of child marriage in NTB have not touched the root of the real problem. Therefore there must be a more comprehensive policy breakthrough to prevent the prevention of child marriage in NTB. There is a need for a legal policy to prevent child marriages in NTB that needs scientific studies as the basis for scientific legitimacy about the urgency of the existence of regional regulations to prevent child marriage. There are two problems in this research, first, What is the juridical problem in the policy of preventing the occurrence of child marriage in NTB? Second, what is the right and applicable policy model in preventing the occurrence of child marriage in NTB? This research is normative legal research with a focus on evaluating the policy of preventing child marriage that has been taken by the NTB provincial government. The research approach used is a normative approach and an empirical approach.The results showed that the first, juridical barriers to preventing child marriage in NTB not only had juridical obstacles in terms of the validity of the provisions of article 7 paragraph (1) of the marriage law that regulates the minimum age of marriage is 16 years for women, but also still has obstacles juridical relating to the legal policy on the regulation of child marriages in the content of regional regulations because the local regulation must not conflict with article 7 paragraph (1) of the marriage law which is still valid and other constraints are not operational and the effective decision of the constitutional court No. 22 / PUU / XV / 2017 concerning judicial review of Law No. 1 of 1974 concerning Marriage because this decision only delayed the implementation of the Constitutional Court's decision in 2021 and was very dependent on legislative policy from the DPR and the President to amend Law No. 1 of 1974 concerning Marriage according to the order of the Constitutional Court's decision. Second, the appropriate and applicable policy model in preventing the occurrence of child marriages in NTB is done using the transitional policy model and post-transition policy. The transition policy is carried out by making regulations that regulate the prevention of child marriages by using the child protection paradigm, while post-transition policies are carried out using the family quality policy paradigm with a focus on increasing the age of marriage. legislation. First, the Republic of Indonesia Parliament, especially the Republic of Indonesia Parliament for the period 2019-2024 and the President should immediately follow up on Decision No. 22 / PUU / XV / 2017 by taking legislative policies by entering the amendment bill to Law No. 1 of 1974 concerning Marriage into a national legislation program which is subsequently compiled, discussed and stipulated as law. Second, to respond to the dynamic dynamics of marital law and child protection, the NTB Governor and the NTB DPRD should immediately take legislation in the regions by including the draft regulation on the prevention of child marriages in the 2019 local regulation formation program and then compile and discuss it into regional regulations.